2023
DOI: 10.1039/d2cp06074d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lattice water molecules on the magnetization dynamics of binuclear dysprosium(iii) compounds: insights from magnetic andab initiocalculations

Abstract: Lattice water effects on the structures and magnetic properties of single-molecule magnets (SMMs) have attracted considerable attention. Herein, we have successfully synthesized two centrosymmetric binuclear compounds [Dy2(2,3′-ppcad)2(C2H3O2)4(H2O)2] (1) and [Dy2(2,3′-ppcad)2(C2H3O2)4(H2O)2]·6H2O...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…First, the different counterions, specifically [Na­(DME) 3 ] + in Er1 , [Li­(DME)] + in Er2 , [Li­(DME) 3 ] + in A , and [K­(DME) 2 ] + in B , are expected to have a certain influence on the QTM relaxation times as discussed in our recent work; the different cations resulted in a ≤5-fold difference in τ QTM . Other reports about the effect of the anion, cation, or guest molecule also show that the nonmagnetic component has a relatively insignificant effect on the magnetic properties of SMMs. Second, Er1 , with its polymeric solid state structure, is expected to exhibit a relaxation behavior different from those of the other discrete complex structures. It has been shown that a polymeric structure can perturb the magnetic relaxations by introducing magnetic exchange coupling. ,, Third, the disparate positioning of the substituents may have also contributed to the observed different behaviors of magnetic relaxation.…”
Section: Resultsmentioning
confidence: 79%
“…First, the different counterions, specifically [Na­(DME) 3 ] + in Er1 , [Li­(DME)] + in Er2 , [Li­(DME) 3 ] + in A , and [K­(DME) 2 ] + in B , are expected to have a certain influence on the QTM relaxation times as discussed in our recent work; the different cations resulted in a ≤5-fold difference in τ QTM . Other reports about the effect of the anion, cation, or guest molecule also show that the nonmagnetic component has a relatively insignificant effect on the magnetic properties of SMMs. Second, Er1 , with its polymeric solid state structure, is expected to exhibit a relaxation behavior different from those of the other discrete complex structures. It has been shown that a polymeric structure can perturb the magnetic relaxations by introducing magnetic exchange coupling. ,, Third, the disparate positioning of the substituents may have also contributed to the observed different behaviors of magnetic relaxation.…”
Section: Resultsmentioning
confidence: 79%
“…Furthermore, the Ni(II) ions in 2 and 3 are wel separated by the (L 1 ) 2− ligand with a separation of 6.0119(1) and 6.0342(1) Å, which doe not favor effective magnetic interaction between Ni(II) ions. The weak intermetallic mag netic interaction, together with the coordination symmetries of single metal ions (espe cially Dy(III) and Tb(III) ion) in 2 and 3, cannot induce enough coercive fields for sup pressing QTM, thus leading to poor magnetic performance of 2 and 3, such as the negligi ble opening of magnetic hysteresis loop and low barrier [48][49][50]. The magnetic interactions between Ln(III) ions in 2 and 3, as well as between Ln(III) ion and Ni(II) ion, are presumably weak because the 4f orbitals of Ln(III) ions are deeply buried and shielded by 5p and 6s orbitals and, thus, cannot effectively overlap with the valence orbitals of bridging atoms [47].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Furthermore, the Ni(II) ions in 2 and 3 are well separated by the (L 1 ) 2− ligand with a separation of 6.0119(1) and 6.0342(1) Å, which does not favor effective magnetic interaction between Ni(II) ions. The weak intermetallic magnetic interaction, together with the coordination symmetries of single metal ions (especially Dy(III) and Tb(III) ion) in 2 and 3, cannot induce enough coercive fields for suppressing QTM, thus leading to poor magnetic performance of 2 and 3, such as the negligible opening of magnetic hysteresis loop and low barrier [48][49][50].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…To construct compounds with SMM performance, selecting suitable organic ligands is of great importance. Acylhydrazone Schiff base ligands have been widely used to construct Dy III -based SMMs with high performance, which can adopt a tridentate chelate coordination mode to coordinate with Dy III ions to form mononuclear and dinuclear compounds with various structures. This versatility is advantageous for fine-tuning the magnetic properties of Dy III -based SMMs via fine-tuning ligand structures or assembly environments. Herein, we choose two tridentate acylhydrazone Schiff bases as ligands, which fine-tune by replacing pyrazine with a pyridine functional group, N 3 -(2-pyrazinyl)-3-pyridinecarboxamidrazone (HL-pyra) and N 3 -(2-pyridoyl)-3-pyridinecarboxamidrazone (HL-pyri).…”
Section: Introductionmentioning
confidence: 99%